EPISTEMOLOGICAL LITERATURE STUDY OF ISLAMIC FINANCE - Bambang Lesmono; Sanusi Gazali Pane; M. Shabri Abd. Majid; Marliyah Marliyah; Rita Handayani (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
This study examined research related to Epistemology of finance in national journal articles. The study used descriptive statistical analysis and narrative reviews based on 30 publication articles with the keyword "Principles of Islamic finance" using Harzing's Publish or Perish application. All sample journal articles have been published. The results showed that there was a diversity of discussions related to "Principles of Islamic finance" published. The largest number of publications is in 2021 as many as 17 articles out of 30 samples of published articles. In general, of the 30 article publications using qualitative approach methods in discussing the "Principles of Islamic finance" as many as 23 articles (76.67%) and quantitative approaches as many as 7 articles (23.33%). Then related to the subject of the study, more related to knowledge / interest with the number of 11 articles (36.67%), then followed by a number of 6 articles (20%) and other themes such as performance which only amounted to 2 articles (6.67%), and others as many as 11 articles (36.67%).